2011
DOI: 10.1007/s00405-011-1605-z
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric powered endonasal dacryocystorhinostomy

Abstract: Dacryocystorhinostomy (DCR) is indicated in children with persistent nasolacrimal duct obstruction (NLDO). Endoscopic endonasal DCR has been successfully performed in both adults and children, with success rates similar to that of external DCR. This paper aims to evaluate the outcomes of paediatric patients undergoing endonasal endoscopic DCR at a district general hospital. A retrospective review of all patients attending a joint lacrimal clinic undergoing endonasal endoscopic DCR between October 2001 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Endocanalicular diode laser DCR is an effective treatment for pediatric patients with congenital NLDO and offers shorter operative time with less morbidity. [21] Another option is endonasal laser (ENL-DCR) which employs potassium-titanyl-phosphate laser. [22] Equipment required for most of these modern surgical methods is unavailable in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Endocanalicular diode laser DCR is an effective treatment for pediatric patients with congenital NLDO and offers shorter operative time with less morbidity. [21] Another option is endonasal laser (ENL-DCR) which employs potassium-titanyl-phosphate laser. [22] Equipment required for most of these modern surgical methods is unavailable in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the series did not specify the cause of NLDO, we found that EDCR, overall, most commonly was warranted in the patients with congenital NLDO ( n = 200). 1218 In one series, however, idiopathic NLDO ( n = 10) was found to be the most common indication for EDCR. 7 Other indications were trauma, iatrogenic causes, craniofacial abnormalities, and infection.…”
Section: Resultsmentioning
confidence: 93%